Genome Sequence of the Fish Pathogen Flavobacterium columnare ATCC 49512 - (:unkn) unknown (AMER SOC MICROBIOLOGY, 2012)
Flavobacterium columnare is a Gram-negative, rod-shaped, motile, and highly prevalent fish pathogen causing columnaris disease in freshwater fish worldwide. Here, we present the complete genome sequence of F. columnare strain ATCC 49512.
Keywords: FLEXIBACTER-COLUMNARIS; NOV